G608(P) Understanding the spiritual and emotional needs of siblings of children with a rare disease from the young person's and parental perspectives. (May 2019) - Nash, P; Bryson, L; Roberts, E; Kerecuk, L; Gray, S; Nash, S
Abstract : Aims: Recent figures show around a fifth of young people identify as young carers 1 . Overall, literature suggests siblings of sick children are at risk of adverse outcomes, with positive outcomes possible with appropriate support. This study aims to identify emotional and spiritual needs of children and young people (CYP) with a sibling with a chronic rare disease and to recommend support strategies to multidisciplinary professionals. Method: The KIDSCREEN-52 questionnaire 2 is a health-related quality of life measure with matched parent and CYP questionnaires. This was completed by parents and siblings. Siblings had a follow up interview and optional focus group. Eligible siblings were aged 8 to 18 years, who had a sibling under 16 with a rare disease. Responses from the questionnaire were analysed in accordance with guidelines 2, based on UK normed data. Transcripts from the interviews and focus groups were coded and thematic analysis undertaken. Results: There was notable disparity between parental and sibling scores in 8 out of 10 areas. Parents rated the sibling below the 50th percentile for 8 out of 10 areas, suggesting a global impact of having a sick sibling. Mean scores for Psychological Wellbeing and Moods and Emotions were in the bottom quarter. Siblings rated themselves below the 50th percentile on only half of the areas. Mean scores for Psychological Wellbeing and Moods and Emotions were on the 50th percentile, but both had wide ranges, showing some siblings having particular difficulties. Mean scores for Peers and Home Life were in the bottom third for both parents and siblings. Emerging themes from focus groups and interviews include: different support needs for younger verses older CYP; need for a safe person to talk to; family days out; activities for siblings in hospital; greater awareness of sibling needs. Conclusion: Notable disparities between parents and siblings' perceptions of need highlights the importance of including CYP in family assessment. Further research is indicated to explore the discrepancies in the scores, how to identify siblings most at risk of adverse outcomes and how to reach older adolescent siblings. Increased age appropriate support is needed in hospitals and schools to reduce adverse outcomes.